The fraud exception in international documentary credit transactions seen from an English and German perspective - Dankert, Oliver (Centre for Law and Society, 2026)
This inquiry will investigate the extent to which fraudulent conduct affects the rules and principles of international documentary credit transactions particularly the issuing or confirming bank's legal position of vis a vis the beneficiary. The inquiry will be taken from the perspective of English and German law, with the main focus on that very important English case, United City Merchants v Royal Bank of Canada1. The legal • position of German law will be compared whether the German solution differs from that found by the House of Lords in United City Merchants v Royal Bank of Canada. Before examining this specific problem in the field of documentary credits, a short survey of the rules, principles and mechanism of documentary credits in international transaction will first be given.